What has been happening to UK income inequality since the mid-1990s? Answers from reconciled and combined household survey and tax return data - Richard V. Burkhauser; Nicolas Hérault; Stephen P. Jenkins; Roger Wilkins (University of Essex, Institute for Social and Economic Research (ISER), 2016)
Estimates of UK income inequality trends differ substantially according to whether estimates are based on household survey data (used for official statistics) or tax return data (used in the top incomes literature). We reconcile differences in variable definitions and combine survey and tax return data in order to take advantage of the much better coverage of top incomes in the latter, and provide improved estimates of UK inequality trends since the mid-1990s. We show there was a marked increase in income inequality in the early 2000s that survey-based estimates do not reveal, and our conclusions are robust to changes in the definitions of income, income-sharing unit, and summary inequality measure. In addition, our reconciled and combined data provide more comparable estimates of UK-US inequality trends than the top incomes literature to date.
Keywords: D31; C81; 330; inequality; income inequality; top income shares; HBAI; SPI; top incomes; tax return data; survey data; Einkommensverteilung; Haushaltsstatistik; Vermögen; Steuerstatistik; Schätzung; Großbritannien; Vergleich; USA